Understanding the relationship between cesarean birth and stress, anxiety, and depression after childbirth: A nationwide cohort study. Issue 4 (8th June 2017) - Chen, Hung‐Hui; Lai, Jerry Cheng‐Yen; Hwang, Shyh‐Jou; Huang, Nicole; Chou, Yiing‐Jenq; Chien, Li‐Yin
Abstract: Background: Women who undergo cesarean birth might have an increased risk for poor mental health after childbirth, possibly because of maternal and neonatal physical problems, low parental confidence, and decreased levels of oxytocin. However, this relationship remains controversial and requires further examination. The study aimed to examine the effect of cesarean birth on postpartum stress, anxiety, and depression. Methods: This nationwide population‐based cohort study was conducted using the Taiwan National Health Insurance Database. A total of 12 619 women who underwent cesarean birth and 12 619 control women who underwent vaginal birth were matched by propensity score based on age, socioeconomic status, residential urbanicity, antepartum comorbidity, and index year of delivery. We compared the incidence of stress, anxiety, and depression during the first postpartum year between cesarean and comparison groups by calculating incidence rate ratios (IRRs). Results: The cesarean group showed a significantly higher risk for stress symptoms (IRR 1.4 [95% confidence interval CI 1.02‐1.92]), but not anxiety (IRR 1.14 [95% CI 0.95‐1.38]) or depression (IRR 1.32 [95% CI 0.94‐1.87]), although the IRRs were also greater than one. The cesarean group had a significantly higher risk of any of the above‐listed three disorders than the comparison group (incidence 27.6 vs 23.4 per 1000 person‐years; IRR 1.18 [95% CI 1.01‐1.38]). Conclusions: Cesarean birth was associated with an increased risk of postpartum stress symptoms. Health professionals should avoid unnecessary cesarean birth, pay attention to women who deliver by cesarean, and intervene appropriately in an attempt to improve mental health among postpartum women.